TABLEWARE DESIGN AS AN ELEMENT OF FOOD CULTURE AND ETHICS: CURRENT TRENDS AND CHALLENGES (Development Service Industry Management, 2025)
This article investigates tableware design as a key element of food culture and ethics in the context of contemporary gastronomic transformations. It explores how the form, color, texture, and material of tableware influence taste perception, trigger emotional reactions, and shape the overall dining experience. Particular attention is given to the phenomenon of multisensory eating, where tableware is viewed not merely as a functional tool but as a medium that engages all human senses. The study highlights ethical dilemmas, especially those related to the manipulative use of visual techniques that alter taste expectations without the consumer’s full awareness. It also addresses the issue of simulated authenticity in restaurant settings, where stylized tableware often replaces genuine cultural tradition, resulting in a form of "ethnographic theater." The article emphasizes the importance of inclusive design, especially the development of functional and aesthetically appropriate tableware for individuals with motor impairments—a need that has become increasingly urgent in the context of the war in Ukraine. Additionally, it examines how digital visual platforms such as Instagram and TikTok are reshaping gastronomic aesthetics, often reducing food consumption to a visual spectacle. In the educational sphere, the article supports the integration of tableware design into Hospitality and Restaurant Management curricula. Drawing on an interdisciplinary approach that combines cultural studies, sensory psychology, design theory, ethics, and service practice, the research offers insights applicable to academic, educational, and professional contexts in the HoReCa industry. Its findings contribute to the development of more ethical, inclusive, and culturally aware models of service.
Keywords: gastronomic authenticity; tableware design; environmental responsibility; consumer ethics; inclusive design; food culture; restaurant service; serviceology; digital aesthetics; HoReCa education